Comparison of combined general anesthesia with complex inhalation and epidural anesthesia for kidney and pancreas transplantation - M. Sh. Khubutiya; S. V. Zhuravel; M. L. Lebedev; A. A. Romanov; A. V. Pinchuk; R. V. Storozhev (Трансплантология (Москва), 2016)
Objective: To determine the efficacy of epidural anesthesia as part of combination inhalation anesthesia in patients undergoing kidney and pancreas transplantationMaterial: The study enrolled 21 patients after combined kidney and pancreas transplantation in in the Sklifosovsky Research Institute for Emergency Medicine.Results: Use of combined inhalation and epidural anesthesia allows for early mobilization of patients after kidney and pancreas transplantation.